Disentangling contributions of point and line defects in the Raman spectra of graphene-related materials. (24th February 2017) - Gustavo Cançado, Luiz; Gomes da Silva, Mateus; Martins Ferreira, Erlon H; Hof, Ferdinand; Kampioti, Katerina; Huang, Kai; Pénicaud, Alain; Alberto Achete, Carlos; Capaz, Rodrigo B; Jorio, Ado
Abstract: The transition from graphene to a fully disordered sp 2 carbon material can be idealized by either cutting graphene into smaller and smaller pieces, or adding more and more point defects. In other words, from the dimensionality standpoint, defects in two-dimensional (2D) systems can be either one- (1D) or zero-dimensional (0D). From an application point of view, both in terms of bottom-up as well as top-down approaches, the discrimination between these two structural disorder in two-dimensional systems is urgently desired. In graphene, both types of defects produce changes in the Raman spectrum, but identifying separately the contribution from each defect-type has not yet been achieved. Here we show that a diagram can be built for disentangling contributions of point-like and line-like defects to the Raman spectra of graphene-related materials embracing, from the topology point of view, all possible structures from perfect to fully disordered sp 2 bonded carbons. Two sets of graphene-related samples, produced by well-established protocols that generate either 0D or 1D defects in a controlled way, are analysed with our model and used to parameterize the limiting values of the phase space. We then discuss the limitations and apply our new methodology to analyse the structure of two-dimensional nanocarbons generated from renewable gas, used to produce inks and conducting coatings.